Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có 13x = \(\frac{13^{17}+13}{13^{17}+1}=1+\frac{12}{13^{17}+1}\)
13y = \(\frac{13^{16}+13}{13^{16}+1}=1+\frac{12}{13^{16}+1}\)
Vì 1317 + 1 > 1316 + 1
=> \(\frac{1}{13^{17}+1}< \frac{1}{13^{16}+1}\)
=> \(\frac{12}{13^{17}+1}< \frac{12}{13^{16}+1}\)
=> \(1+\frac{12}{13^{17}+1}< 1+\frac{12}{13^{16}+1}\)
=> 13x < 13y
=> x < y
Vậy x < y
\(\frac{x}{19}=\frac{19^{17}+1}{19^{17}+19}=1-\frac{18}{19^{17}+19}\)
\(\frac{y}{19}=\frac{19^{16}+1}{19^{16}+19}=1-\frac{18}{19^{16}+19}\)
Nhận thấy 1917 + 19 > 1916 + 19
=> \(\frac{18}{19^{17}+19}< \frac{18}{19^{16}+19}\)
=> \(-\frac{18}{19^{17}+19}>-\frac{18}{19^{16}+19}\)
=> \(1-\frac{18}{19^{17}+19}>1-\frac{18}{19^{16}+19}\)
=> \(\frac{x}{19}>\frac{y}{19}\)
=> x > y
Vậy x > y
Ta có : \(\frac{x}{19}=\frac{19^{17}+1}{19^{17}+19}=1-\frac{18}{19^{17}+19}\)
\(\frac{y}{19}=\frac{19^{16}+1}{19^{16}+19}=1-\frac{18}{19^{16}+19}\)
Vì\(\frac{18}{19^{17}+19}< \frac{18}{19^{16}+19}\)\(\Rightarrow\frac{x}{19}>\frac{y}{19}\)
mà \(x,y>0\)
\(\Rightarrow x>y\)
a) Ta có \(\left(2^{17}+17^2\right)\cdot\left(9^{15}-15^9\right)\cdot\left(4^2-2^4\right)\)
=\(\left(2^{17}+17^2\right)\cdot\left(9^{15}-15^9\right)\cdot\left(16-16\right)\)
=\(\left(2^{17}+17^2\right)\cdot\left(9^{15}-15^9\right)\cdot0\)=0
b) \(\left(7^{1997}-7^{1995}\right):\left(7^{1994}\cdot7\right)\)
=\(\left(7^{1995}\left(7^2-1\right)\right):7^{1995}\)
=\(7^2-1\)=\(49-1\)=\(48\)
c Giống câu a
Ta có: x = \(\frac{7^{16}-3}{7^{16}+1}=\frac{7^{16}+1-4}{7^{16}+1}=1-\frac{4}{7^{16}+1}\)
y = \(\frac{7^{17}-3}{7^{17}+1}=\frac{7^{17}+1-4}{7^{17}+1}=1-\frac{4}{7^{17}+1}\)
Do \(7^{16}+1< 7^{17}+1\) => \(\frac{4}{7^{16}+1}>\frac{4}{7^{17}+1}\) => \(-\frac{4}{7^{16}+1}< -\frac{4}{7^{17}+1}\)
=> \(1-\frac{4}{7^{16}+1}< 1-\frac{4}{7^{17}+1}\) => x < y
Trả lời:
\(x=\frac{7^{16}-3}{7^{16}+1}=\frac{7^{16}+1-4}{7^{16}+1}=\frac{7^{16}+1}{7^{16}+1}-\frac{4}{7^{16}+1}=1-\frac{4}{7^{16}+1}\)
\(y=\frac{7^{17}-3}{7^{17}+1}=\frac{7^{17}+1-4}{7^{17}+1}=\frac{7^{17}+1}{7^{17}+1}-\frac{4}{7^{17}+1}=1-\frac{4}{7^{17}+1}\)
Ta có: \(7^{16}< 7^{17}\)
\(\Leftrightarrow7^{16}+1< 7^{17}+1\)
\(\Leftrightarrow\frac{4}{7^{16}+1}>\frac{4}{7^{17}+1}\)
\(\Leftrightarrow-\frac{4}{7^{16}+1}< -\frac{4}{7^{17}+1}\)
\(\Leftrightarrow1-\frac{4}{7^{16}+1}< 1-\frac{4}{7^{17}+1}\)
\(\Leftrightarrow x< y\)
Vậy x < y